INVESTIGATION OF FREE SURFACE EFFECTS OF A 2-D SOURCE MOVING WITH CONSTANT VELOCITY - Dogrul, Ali; Bal, Sakir; Celik, Fahri (YILDIZ TECHNICAL UNIV, 2015)
Wave resistance is the most important component of ship total resistance especially in high speeds. In this study, the wave deformations generated on the free surface by a 2-D point source moving under the free surface are investigated in order to create a basis to the calculation of ship wave resistance and wave deformations around ship. In this manner, the flow problem is solved numerically with boundary element method (BEM) by means of potential flow theory. In the study, the free surface boundary condition is modeled in first, second and third order and the results are computed for different submergence depths in Fn=0.6. As a result, the non-dimensional depth coefficient consisting of the depth, Froude number and source strength is proposed to determine the depth and Froude number in which all the results are in good agreement.
Keywords: Wave deformation; potential flow theory; BEM; 2-D source; free surface; Engineering